Passion fruit (Passiflora edulis): Nutritional composition, bioactive compounds, utilization of by-products, biocontrol, and organic fertilization in cultivation - Campos-Rodriguez, Jordy (2023)
Passion fruit (Passiflora edulis) is a tropical fruit appreciated for its attractiveness and nutritional value. The yellow variety (Passiflora edulis f. flavicarpa) and the purple variety (Passiflora edulis f. edulis) are the best-known species, both rich in carbohydrates, proteins, lipids and bioactive compounds. Despite their potential, passion fruit by-products, such as seeds and peel, are underutilized, despite being sources of phenolic compounds and carotenoids. The leaves are considered insignificant, yet they contain nutrients and medicinal effects beneficial to health. Nevertheless, these by-products have diverse uses and applications. In this sense, this work seeks to document research on passion fruit and its by-products, emphasizing their composition and possible uses in agroindustrial products. In addition to propose pest biocontrol strategies to preserve the quality of the crop and the implementation of organic fertilizers in crops, promoting sustainable agricultural practices. In this sense, it is urgent not only to diversify the agroindustry and develop new products, but also to contribute to the reduction of environmental impact and promote sustainable agricultural practices. The integrated use of passion fruit emerges as a key strategy for moving towards more efficient and sustainable production.